Paired T-Test to Determine the Effect of Smart Paperboard Learning Media on Student Learning Outcomes in the Subject of Islamic Cultural History - Wardani, Dian Kusuma; Shokiba, Meiga Nurhalizah; Chotimah, Chusnul; Istiana, Istiana (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This study aims to determine and measure the impact of smart paperboard learning media integration on student learning outcomes in the Islamic Cultural History (SKI) subject at MA Mambaul Ulum Megaluh Jombang. Both students and teachers utilized this learning media during the teaching and learning process. A quantitative research method with paired t-test analysis was employed in this study. Data was collected through pre-test, post-test, and observation towards the students of Class X AB at MA Mambaul Ulum Megaluh Jombang as research participants. Before conducting the paired t-test, a normality test was performed, which resulted in a value of 0.109 > 0.05, indicating that the data is normally distributed. The results of the paired t-test analysis showed a significance value of 0.00 < 0.05, meaning that the smart paperboard learning media has a positive effect on student learning outcomes. The findings of this study strengthen the theory that using cutting-edge and interactive learning media, such as smart paperboard, can foster the effectiveness of learning. Likewise, this study implies that active student participation in the learning process positively contributes to enhancing their learning outcomes.